2007
DOI: 10.1124/jpet.107.131656
|View full text |Cite
|
Sign up to set email alerts
|

Studies with an Orally Bioavailable αV Integrin Antagonist in Animal Models of Ocular Vasculopathy: Retinal Neovascularization in Mice and Retinal Vascular Permeability in Diabetic Rats

Abstract: The ␣ V integrins are key receptors involved in mediating cell migration and angiogenesis. In age-related macular degeneration (AMD) and diabetic retinopathy, angiogenesis plays a critical role in the loss of vision. These ocular vasculopathies might be treatable with a suitable ␣ V antagonist, and an oral drug would offer a distinct advantage over current therapies. (3,S,␤,S)-1,2,3,4-Tetrahydro-␤- [[1-[1-oxo-3-(1,5,6,7-tetrahydro-1,8-naphthyridin-2-yl)propyl]-4-piperidinyl]methyl]-3-quinolinepropanoic acid (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 41 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…Another antagonist of αv integrins, JNJ-26076713 (a small molecule type antagonist) that is orally available, is worth mentioning here. This antagonist was also found to be very effective in the prevention of retinal neovascularization in mice model of ROP [92].…”
Section: E) Role In Ocular Diseasementioning
confidence: 91%
“…Another antagonist of αv integrins, JNJ-26076713 (a small molecule type antagonist) that is orally available, is worth mentioning here. This antagonist was also found to be very effective in the prevention of retinal neovascularization in mice model of ROP [92].…”
Section: E) Role In Ocular Diseasementioning
confidence: 91%
“…These findings can potentially explain the different time-windows that are used to perform the retinal vascular leakage read-out in the diabetic rat STZ model. Some research groups already assess the permeability level in the diabetic rat eyes approximately 2 weeks after STZ injection [70,73,75,104], while most groups determine the increased leakage level after a longer period of hyperglycemia even up to 6 months postinjection [61, 69,96,105,106].…”
Section: Diabetic Modelsmentioning
confidence: 99%
“…rat VEGFinduced retinal permeability model [71,107], the quantitative Evans Blue method is also often applied in the diabetic rodent STZ model [71,98,104]. Several studies have demonstrated that perfusion with FITC-conjugated albumin or dextran in STZ-induced diabetic animals is a reliable technique to assess retinal permeability quantitatively [69,106,108,109] (Figure 1).…”
Section: Diabetic Modelsmentioning
confidence: 99%
“…Recent experiments elucidating the extracellular ''interactome'' of the FGF receptor-ligand system have shown that ECM receptors act as noncanonical co-receptors that impart specificity to FGF signaling (Polanska et al, 2008). For example, inhibition of alpha V integrin can block FGF induced cell adhesion, migration, and angiogenesis (Rusnati et al, 1997;Santulli et al, 2008). This type of regulation provides mechanistic insight into how crosstalk between cell adhesion receptors and signaling pathways mediates cellular behavior.…”
Section: Broad Functions Of Cell-ecm Adhesion Cell-ecm Interactions Rmentioning
confidence: 99%